Discurso da beleza na publicidade digital - Nunes, Wanderla Corrêa de Paula Nassif (2008)
The new technologies of the information and the knowledge provided the sprouting of a new mean of information: the Internet. Cyberspace, as it is called by many scholars, provoked diverse changes in the scope of social, economic, cultural, ideological relations, among others, therefore it is a way that allows to the interaction and the contact of an individual with the other, of several with several, of few with many, few with few and many with many. The use of this space is reality as media that imposes new forms to see, of being, making, to read, to write, to understand and to interpret the world and what in it encircles us. In this way, all of us were affected, because the techniques are easy to use: to inform, to talk and to surf in the Internet became daily action for many. However to know as it makes this discursive process, as well as its effect of direction in this new support, is very complex. We don’t have it very clear and defined how all the changes had occurred yet and how everything affected and still affect our lives. Today many scholars defend that it must be reinvent advertising discourse and, consequently, how to see, to read and to interpret the advertising. The advertising discourse, some time ago, was made in an authoritarian, manipulating, seductive and rhetorical way of speech, but with the arrival of the Internet the advertising made of one for all, started to construct one another relation that would be the participation of the public in the construction of the proper speech advertising, because currently the support of the Internet provides apparently the freedom of the user choices. Faced with this, this study has for purpose to verify which digital discursive practices and identities, on the female beauty, that emerge of the Dove cosmetic products advertising site and which are their effects of meaning. Analyzing the digital discursive practices and identities in the site, were chosen the analysis of speech of the French school as referential theoretician. The object of this theoretical perspective, established in 1969, in France, for Michel Pêcheux, is the speech, which according to author is understood as a way of effect between speakers. Moreover, the study used authors who had contributed to reflect on the identity in the after-modernity and the advertising in web, such as: Foucault (1977, 1979, 1985, 1990, 1994, 1997, 1999, 2001, 2007) for the identities practices, specifically the techniques of itself, Bauman (1998, 2001, 2005) for the question of the identity in the after-modernity, Lemos (2004) and Lévy (1998, 1999) in which refers to the Internet and Carvalho (1996) for the advertising speech. In the analysis, the functioning of the speech of the beauty was observed as a constructor of feminine selfesteem in consumers statements left in Dove digital section – Consumers statements. Discursive strategies such as the paraphrase and the ambiguity are present for Dove products user to accept its condition of natural beauty, therefore this does not appear in the body, but in the essence and in the values that each person possess. Keywords: Speech. Identity. Beauty. Advertising. Self esteem.